Virtual network embedding algorithm based on consultant guided search - Wentan LIU; Lei ZHUANG; Mengyang HE; Shuaikui TIAN; Yu SONG; Guoqing WANG (物联网学报)
Considering at the problem of virtual network embedding,a virtual network embedding algorithm based on consultant guided search was proposed.The CPU of node,node degree and adjacent bandwidth were considered comprehensively,and the virtual network embedding was carried out with the meta-heuristic consultant guidance search.Experimental results show that compared with EAJTA-VNE algorithm and ANT-VNE algorithm,the proposed CGS-VNE algorithm has a higher request acceptance rate and revenue-cost ratio,and the embedding time in the context of low,medium and high resource demand of virtual network requests is shorten.